The Relationship Between Concentration And Top Serve Accuracy And Bottom Serve In Volleyball - Refalda Herista; Sucipto Sucipto; Ahmad Hamidi (Universitas Negeri Semarang, 2026)
The game of Volleyball is one of the sports that is widely taught in schools and developed competitively. One of the basic techniques that plays an important role in the game of volleyball is serve, which consists of an upper serve and a lower serve. Concentration is a psychological factor that is suspected to affect the accuracy of the serve because the player must be able to coordinate body movements, regulate the power of the shot, and direct the ball to the target precisely. This study aims to determinethe relationship between concentration and the accuracy of the upper serve and the bottom serve in the game of volleyball. This study uses a quantitative descriptive method with a correlational design. The research sample consisted of 15 extracurricular volleyball male athletes of SMAN 10 Bandung who were selected using purposive sampling techniques. The instruments used are the Grid Concentration Test (GCT) to measure concentration and AAHPER Serving Accuracy Test to measure service accuracy. The data wasanalyzed using the Pearson Product Moment correlation test. The results showed that the relationship between concentration and bottom service accuracy was very low and insignificant (r = 0.125; p = 0.657). Meanwhile, the association between concentration and upper serve accuracy showed a stronger, but also less statistically significant correlation (r = 0.480; p = 0.070). The determination coefficient (R² = 0.231) showed that concentration contributed 23.1% to the variation in service accuracy. It was concluded that concentration tends to have a greater role in the upper serve than the lower serve due to its higher complexity of motion. However, no statistically significant relationship was found between concentration and service accuracy in this study sample.